Effect of temperature on the degree of anatase-rutile transformation in titanium dioxide nanoparticles synthesized by the modified sol-gel method - Wetchakun N. (2014)
Modified sol-gel method was used to synthesize high purity titanium dioxide (TiO2) nanoparticles. The TiO2 nanoparticles were synthesized by hydrolysis and condensation of titanium tetraisopropoxide in absolute ethanol using cellophane membrane. The use of cellophane membrane offers the advantage of well-controlled diffusion rate. Phase transformation, crystallite size, and phase composition of the calcined TiO2 nanoparticles were derived from X-ray diffraction analysis by fundamental approach and the Rietveld method. The Brunauer, Emmett and Teller (BET) adsorption-desorption of nitrogen gas for specific surface area determination at the temperature of liquid nitrogen was performed on TiO2 samples. The sample of pure anatase calcined at 400 °C for 3 h possessed high specific surface area of 121 m2/g. The particles morphology of the samples was examined by transmission electron microscopy (TEM). The crystallite sizes of anatase phase increased from 15 nm at 400 °C to 60 nm at 700 °C. The photocatalytic activities of TiO2 nanoparticles were investigated with oxalic acid, formic acid, and malonic acid. Under near-UV irradiation, it was found that TiO2 nanoparticles calcined at 400 °C for 3 h showed the highest activity for mineralizing oxalic acid. © 2007 Elsevier B.V. All rights reserved.